2001
DOI: 10.1021/bi010087g
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of the Conserved Key Residue Arginine 209 in Neuronal Nicotinic Receptors

Abstract: We have examined the role of a highly conserved arginine (R209), which flanks the M1 transmembrane segment of nAChRs, in the biogenesis and function of neuronal nAChRs. Point mutations revealed that, in alphaBgtx-sensitive neuronal alpha7 nAChRs, the conserved arginine is required for the transport of assembled receptors to the cell surface. By contrast, R209 does not play any role in the transport of assembled alpha-Bgtx-insensitive neuronal alpha3beta4 nAChRs to the cell surface. However, a basic residue at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…This functionally important interaction can be restored by the proposed disulfide bond in the Asp-148 3 Cys,Arg-218 3 Cys double mutant. Second, and in agreement with previous studies on the equivalent residue of different nAChRs (38,51) and ␣1 GlyR Arg-218 (26), ␣1 GlyR Arg-218 is important for channel expression. Our data show that in contrast to the functionally relevant salt bridge with Asp-148, which can be mimicked by the proposed disulfide bond, the positive charge of Arg-218 is required for efficient expression, as the Asp-148 3 Cys,Arg-218 3 Cys double mutant, although functionally similar to WT, shows dramatically reduced expression levels ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This functionally important interaction can be restored by the proposed disulfide bond in the Asp-148 3 Cys,Arg-218 3 Cys double mutant. Second, and in agreement with previous studies on the equivalent residue of different nAChRs (38,51) and ␣1 GlyR Arg-218 (26), ␣1 GlyR Arg-218 is important for channel expression. Our data show that in contrast to the functionally relevant salt bridge with Asp-148, which can be mimicked by the proposed disulfide bond, the positive charge of Arg-218 is required for efficient expression, as the Asp-148 3 Cys,Arg-218 3 Cys double mutant, although functionally similar to WT, shows dramatically reduced expression levels ( Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…The idea of an electrostatic interaction between Asp-148 and Arg-218 is further supported by another study that suggested an interaction between the equivalent residues in the ␤2 subunit of GABA A receptors (12). The proposed interaction between Asp-148 and Arg-218 in the ␣1 GlyR is of particular interest as mutations at side chains equivalent to ␣1 GlyR Arg-218 have been shown to be crucial for channel function in different pLGICs (12,15,38,(51)(52)(53) and especially because the ␣1 GlyR Arg-218 3 Gln mutation can give rise to the inherited hyperekplexia or startle disease (26). The idea that Arg-218 contributes to a salt bridge crucial for channel gating in the native receptor provides an explanation for molecular basis for a pathophysiologically relevant mutant; the neutral Arg-218 3 Gln mutation would prevent the formation of a strong salt bridge and, hence, give rise to the drastic effect on gating observed with this mutant.…”
Section: Discussionmentioning
confidence: 86%
“…This motif starts at a position equivalent to Pro 207 in V201 and, therefore, is located at a 5-amino acid distance from Ile 202 downward from the C terminus. Moreover, we have previously shown that an arginine (Arg 205 according to the numbering system used here) located between Ile 202 and the latter motif and conserved in all ligand-gated channel subunits is required for transport of assembled ␣7 receptors to the cell surface (31). Also in this region certain domains have been found that affect surface expression of ␣7-5HT 3 chimeric receptors (32).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, ␤ 2 R216 appears to be a key player. This residue is absolutely conserved in every member of the Cys-loop receptor superfamily, and its mutation has been shown to alter agonist-induced channel gating in other Cys-loop receptors (Vicente-Agullo et al, 2001;Hu et al, 2003;Castaldo et al, 2004). A model of the GABA A receptor shows ␤ 2 R216 in close proximity to ␤ 2 E52 (Fig.…”
Section: Discussionmentioning
confidence: 99%